Responsibilities of the Board of Directors in the Bankruptcy of the Limited Liability Company - Padriadi Wiharjokusumo; Novita Romauli Saragih (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
Article 97 paragraph (1) of the Company Law requires each member of the Board of Directors to be required in good faith and full responsibility to undertake the supervision of the company for the interests and business of the company. This implies the Board of Directors is liablefor each management and representation of the company in the company’s framework in pursuing its purposes and objectives.This researchexaminesthe responsibilities of the board of Directors in the bankruptcy of the Limited Liability Company based on Law No. 40 of 2007. This research was conducted through a normative juridical approach.The data source of this research was gained from the library study. Then it was analyzed using the qualitative analysis which depicts and dissects the significant information.The conclusion of this research is thatthe responsibilities of the Board of Directors in Bankruptcy Limited Liability Company based on Law No. 40 of 2007 comprises 2 (two) aspects, in particular; civil liability and criminal liability.